Pengembangan Media Buku Interaktif Bahasa Indonesia "Satu Titik" Guna Meningkatkan Minat Belajar Peserta Didik Kelas IV Sekolah Dasar - Salwa, Ulfatus; Rhomadhona, Lola Priyan; Ervianto, Dela Nabila Putri; Witono, Moch Hadi; Rahmawati, Suci; Istiq’faroh, Nurul; Zahroh, Ulfi Aminatuz (Tumoutou Social Science Journal, 2025)
Developing interactive Indonesian language books that suit the needs of grade IV elementary school students using the Research and Development (R&D) method. The results of the study produced an interactive book equipped with various interactive features. This interactive book has been validated by teachers and tested on grade IV students. The results of the trial showed that the interactive book developed was effective in increasing students' learning motivation towards the use of interactive books in learning Indonesian. The research method used was descriptive qualitative with data collection through interviews and questionnaires. The results showed that most students had a positive perception of the use of interactive books.